Synchronized expression of FLOWERING LOCUS T between branches underlies mass flowering in Fagus crenata. Issue 1 (30th December 2018) - Satake, Akiko; Kawatsu, Kazutaka; Chiba, Yukako; Kitamura, Keiko; Han, Qingmin
Abstract: Masting is the intermittent and synchronized production of a large amount of flower and seed in plant populations. This population‐level phenomenon is caused by individual‐level variability in reproduction and its synchrony between individuals. The variability at the individual level is induced by synchronized reproduction between branches within an individual because a tree is an assemblage of branches that are considered as semiautonomous units. However, there have been no empirical studies that quantify the degree of reproductive synchrony at the branch level within the same tree in masting species. Here, we evaluated the reproductive synchrony within individuals by monitoring flowering dynamics and expression level of a flowering‐time gene at the branch‐level in a typical masting species, Fagus crenata Blume. The 4‐year census showed that the branch‐level gene expression was highly variable between years and was strongly synchronized between branches. The branch‐level synchrony in flowering‐time gene expression was followed by coherent flowering cycle at the whole individual. To examine the causal relationship between gene expression and climatic factors, we performed a nonlinear statistical analysis called convergent cross‐mapping using the time course data of gene expression and environmental variables. Our results indicated that the observed gene expression pattern was well cross‐mapped by temperature or precipitation. However, this cross‐mapping skill was lower than that of randomly generated seasonal dynamics, implying a combination of internal and external environmental signals is more likely to regulate gene expression dynamics in F. crenata . Our results provide the first empirical evidence that synchronized expression of a flowering‐time gene between branches underlies integrated flowering behavior at the individual level. Abstract : We evaluated the reproductive synchrony within individual tree by monitoring flowering dynamics and expression level of a flowering‐time gene at the branch‐level in a typical masting species, Fagus crenata Blume. Synchronized expression of a flowering‐time gene between branches underlies integrated flowering behavior at the individual level.